2020
DOI: 10.3389/fphy.2020.602229
|View full text |Cite
|
Sign up to set email alerts
|

Breather Structures and Peregrine Solitons in a Polarized Space Dusty Plasma

Abstract: In this theoretical investigation, we have examined the combined effects of nonthermally revamped polarization force on modulational instability MI of dust acoustic waves DAWs and evolution of different kinds of dust acoustic (DA) breathers in a dusty plasma consisting of negatively charged dust as fluid, Maxwellian electrons, and ions obeying Cairns’ nonthermal distribution. The nonthermality of ions has considerably altered the strength of polarization force. By employing the multiple-scale perturbation tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 62 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…Dusty plasmas have been found to support nonlinear DIA freak or rogue waves which are the rational solution of the nonlinear Schrödinger equation (NLSE) [833]. Singh and Saini [834] have shown that modulational instability of DA waves can give rise to different kinds of DA breathers and rogue waves in a dusty plasma system comprising negatively charged dust, Maxwellian electrons, and nonthermal ions. On the other hand, the presence of dust is shown to have a damping effect on stellar wind-driven instability [835].…”
Section: Space Dusty Plasmasmentioning
confidence: 99%
“…Dusty plasmas have been found to support nonlinear DIA freak or rogue waves which are the rational solution of the nonlinear Schrödinger equation (NLSE) [833]. Singh and Saini [834] have shown that modulational instability of DA waves can give rise to different kinds of DA breathers and rogue waves in a dusty plasma system comprising negatively charged dust, Maxwellian electrons, and nonthermal ions. On the other hand, the presence of dust is shown to have a damping effect on stellar wind-driven instability [835].…”
Section: Space Dusty Plasmasmentioning
confidence: 99%
“…In the context of plasma fluids, the NLS equations has been derived for the first times in the early '70s [8,9], and subsequently for a large variety of electrostatic plasma models. Recently, its localized solutions (envelope solitons, breathers) have in fact been associated with freak or rogue waves in plasmas [10,11,12,13]. Formally analogous NLS equations focusing on electromagnetic waves in plasmas modeled by fluid-Maxwell equations have been also derived [14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…have revealed the universality of non-Maxwellian velocity distributions, [3][4][5][6][7][8][9][10] such as the familiar kappa-distribution and the kappa-like distributions in suprathermal space plasmas, [3,4] the power-law q-distribution in nonextensive statistics, [5] and the non-thermal α-distribution in solitary structures observed by the Freja satellite [6] etc, which in some physical situations have significantly different natures from those plasmas with a Maxwellian distribution. The non-thermal α-distribution is important because it may change the nature of ion sound solitary structures and allow the existence of structures very like those observed, [6] and thus widely affect other properties in various types of plasmas including dusty plasmas, such as shear-flow driven tripolar vortices, [11] solar wind interaction with dusty plasmas, [12] polarized space dusty plasmas, [13] dust-acoustic solitary waves, [14] shear-flow driven dissipative instability, [15] and Landau damping in dust-acoustic waves [16] etc.…”
Section: Introductionmentioning
confidence: 99%